Recent Advances on Principles of Concurrent Data Structures. - Castañeda, Armando; Rajsbaum, Sergio (Communications of the ACM, 2024)
This article details the recent advances in concurrent data structures in the authors' research group at the Instituto de Matemáticas of the Universidad Nacional Autónoma de México. The article discusses linearizability and how this research group is working to overcome its limitations including their work with interval-linearizability.